An Efficient and Environmentally Benign Protocol for the 1, 6‐Michael Addition of Nitroalkanes to 3‐Methyl‐4‐nitro‐5‐styrylisoxazoles in WERSA. Issue 6 (13th February 2018) - Kumar, Nandigama Satish; Bheeram, Vema Reddy; Mukkamala, Saratchandra Babu; Rao, L. Chandrasekhara; Vasantha, R.
Abstract: Herein, we describe a mild and convenient protocol for Michael addition of nitroalkanes to 3‐methyl‐4‐nitro‐5‐styrylisoxazoles using neat "water extract of rice straw ash (WERSA)" as a catalyst and medium at room temperature. Method developed is simple to operate and yields range from good to excellent. This eco‐friendly protocol also successfully used for the synthesis of pharmaceutical interest, such as γ‐nitrobutyricacid an intermediate for the preparation of Baclofen. Abstract : Herein, we describe a mild and convenient protocol for Michael addition of nitroalkanes to 3‐methyl‐4‐nitro‐5‐styrylisoxazoles using neat "water extract of rice straw ash (WERSA)" as a catalyst and medium at room temperature. Method developed is simple to operate and yields range from good to excellent. This eco‐friendly protocol also successfully used for the synthesis of pharmaceutical interest, such as γ‐nitrobutyricacid an intermediate for the preparation of Baclofen.